Optimal allocation model of logistics alliance resources based on willingness to participate - Mengrong LI; Huayu ZHU; Jin QI; Yanfei SUN (物联网学报)
In order to reduce the costs and improve the efficiency during large-scale logistics tasks, logistics alliances are established by enterprises to achieve scale effects.The stability of the cooperative operation of the logistics alliances is mainly reflected in the enthusiasm of enterprises for participating in cooperation.Therefore, a resource optimal allocation model based on the willingness to participate was proposed, considering the impact of the participation willingness of alliance members on the resource allocation of the alliance.A sorting method with the optimal solution based on the regret theory was proposed to solve the model, and the method was verified based on the participation willingness index.The results show that the participation willingness distribution score of the sorting method based on the regret theory is 3.5 times higher than that of the traditional method.It can be seen that the proposed method can effectively improve the scientificity and rationality of resource allocation, and can contribute to consolidate the stability of the collaborative operation of the supply chain.